Identification and characterization of the zebrafish glutathione S‐transferase Pi‐1. Issue 10 (16th June 2017) - Abunnaja, Maryam S.; Kurogi, Katsuhisa; Mohammed, Yasir I.; Sakakibara, Yoichi; Suiko, Masahito; Hassoun, Ezdihar A.; Liu, Ming‐Cheh
Abstract: Zebrafish has in recent years emerged as a popular vertebrate model for use in pharmacological and toxicological studies. While there have been sporadic studies on the zebrafish glutathione S‐transferases (GSTs), the zebrafish GST gene superfamily still awaits to be fully elucidated. We report here the identification of 15 zebrafish cytosolic GST genes in NCBI GenBank database and the expression, purification, and enzymatic characterization of the zebrafish cytosolic GST Pi‐1 (GSTP1). The cDNA encoding the zebrafish GSTP1 was cloned from a 3‐month‐old female zebrafish, expressed in Eschelichia coli host cells, and purified. Purified GSTP1 displayed glutathione‐conjugating activity toward 1‐chloro‐2, 4‐dinitrobenzene as a representative substrate. The enzymatic characteristics of the zebrafish GSTP1, including pH‐dependency, effects of metal cations, and kinetic parameters, were studied. Moreover, the expression of zebrafish GSTP1 at different developmental stages during embryogenesis, throughout larval development, onto maturity was examined.